Systèmes agraires et changement climatique au Sud - Cochet, Hubert; Ducourtieux, Olivier; Garambois, Nadège (éditions Quae, 2019)
Based on the comparative study of local, contrasting situations in Sub-Saharan Africa and South-East Asia, this book highlights the processes that explain the tremendous exposure to hazards of various farmer groups and their unequal ability to adapt. It sets out modalities for adjusting to global changes and sketches proposals for political measures to support the producers.